The potential role of interleukin (IL)‐25/IL‐33/thymic stromal lymphopoietin (TSLP) on the pathogenesis of idiopathic pulmonary fibrosis. (9th September 2022) - Xu, Xuefeng; Dai, Huaping; Zhang, Jinglan
Abstract: Objectives: Interleukin (IL)‐25, IL‐33, and thymic stromal lymphopoietin (TSLP) are the important drivers for excessive type‐2 immunity. It has been well elucidated that IL‐25/IL‐33/TSLP plays an important role in allergic airway inflammation and remodeling, whereas their roles in idiopathic pulmonary fibrosis (IPF) still remained largely unclear. Herein, the aim of the review is to discuss the potential role and mechanism of IL‐25/IL‐33/TSLP on IPF by literature analysis and summary. Data source: We have done a literature search using the following terms: ("idiopathic pulmonary fibrosis" OR "IPF" OR "lung fibrosis") and (TSLP or "thymic stromal lymphopoietin" or IL‐25 OR IL‐17E OR IL‐33) from the database of PubMed published in English up to July 2018. Study selection: We have totally found 58 articles by using the retrieval terms mentioned above. By careful title and abstract reading, 10 original research articles of high quality were enrolled for the full text reading and analysis. Two additional relevant studies were also included during the course of literature readings. Results: IL‐25/IL‐33/TSLP and their corresponding receptors, that is, IL‐17BR/ST2L/TSLPR, are shown to be up‐regulated both in IPF patients and bleomycin (BLM)‐induced lung fibrosis mice model. IL‐25 may promote lung fibrosis by activating IL‐17BR+fibroblast and IL‐17BR+ILC2 (type 2 innate lymphoid cell). Full length (fl)‐IL‐33, as a transcription factor mainly in the cell nucleus, mediated non‐atopic lung inflammation and fibrosis by modulating expressions of several pro‐fibrotic mediators, including transforming growth factor (TGF)‐b1. By contrast, mature (m)‐IL‐33 potentiates lung fibrosis by recruiting ST2L+M2 macrophages and ST2L+ILC2 to enlarge type 2 immunity. TSLP was shown to directly promote CCL2 expression in primary human lung fibroblasts (pHLFs). Conclusion: IL‐25/IL‐33/TSLP contributes to non‐allergic lung fibrosis by mediating persistent abnormal epithelial‐mesenchymal crosstalk. IL‐25/IL‐33/TSLP may serve the promising novel target for the treatment of IPF. Abstract : Interleukin (IL)‐25/IL‐33/thymic stromal lymphopoietin (TSLP) derived from alveolar epithelial cells (AECs) can initiate an abnormal, profibrotic crosstalk to mesenchymal cells (including fibroblasts, dendritic cell [DCs], M2‐macrophage, and type 2 innate lymphoid cells [ILC2s]) and thereby leads to lung fibrosis.